Pengaruh Pyhsical Evidence, Lokasi dan Harga Terhadap Keputusan Loyalitas Pelanggan Pada Green Cafe Kota Bima - Raflin Setiawan; Ita Purnama; Sri Ernawati (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
contains: (1) To determine whether there is a significant simultaneous influence between physical evidence, location and price on customer loyalty decisions at the Green Cafe in Bima City,(2) This type of research is associative, the instrument in this research is using a questionnaire with a Likert scale, the population is all the people of the city of Bima who have visited the green cafe, the number of which cannot be known (unown population) where the sample in this study is 96 with purposive sampling technique, data collection technique, namely through observation, questionnaires and literature study with data analysis techniques, namely: validity test, reliability test, classical assumption test, multiple linear regression test, multiple correlation coefficient, determination, t test and f test (3) The results of this research are physical evidence, location and price have a significant effect on customer loyalty at the Green Cafe, Bima City.